Study on Butterfly Diversity in the Campus of Government College Quepem, Goa, India - Bepari , Sania; Pandit , Rupali; Dharwadkar , Mangirish; Rao , Kulkarni Rajender (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Butterflies belonging to the class Insecta and the order Lepidoptera make the second largest order after Coleopterans. They are one of the best environmental indicators due to their short life cycle and quick response to the changes in the environment. Moreover, they play vital roles in nutrient cycling and food chain in the ecosystems. No published documentary evidences are available on the butterfly diversity of Quepem at the foothills of Western Ghats in Goa. Present study was designed to generate the preliminary checklist of butterflies at the campus of Government College, Quepem. Field survey on butterflies was carried out from September 2021 to January 2022, in the selected sites comprising of botanical garden, butterfly garden and specific sites in the college campus rich in vegetation. 40 butterfly species belonging to five families spread over 30 genera were recorded during the study period. Family Nymphalidae dominated the college campus with 18 species followed by Lycaenidae (9 species), Papilionidae (5 species), and Hesperiidae and Pieridae with 4 species each. The dominance exhibited by family Nymphalidae was mainly due to the rich landscape and the availability of larval host and nectar plants in the campus.